Increasing role of creative personality in development of network society - Babosov, Evgenii M. (Journal of the Belarusian State University. Sociology, 2019)
The role of the creative personality is highlighted; its key qualities are characterized. The functioning and development of the network society and its basic elements are considered. The model of the network-centered system applied to military actions is suggested. The idea that the creative personality in his interactions with the environment serves the main subject of all socio-structural transformations is given grounds for.
Keywords: creative personality; network society; social mechanisms; creative thinking; innovative activity